The leisure factor in entrepreneurial success - a lesson from the robber baron era - Ross, BW (Economic & Social Studies, 1989)
Success in capitalist enterprise is often held to be due to hard work and in particular is usually associated with the Protestant work ethic. However, study of three major entrepreneurs, Carnegie, Rockefeller, and Morgan, reveals systematic leisure seeking and limited involvement in day-to-day business operations. It is suggested that this detachment was an ingredient in their success, enabling more effective decision making. All three relied on hard working and gifted partners but were kept informed by frequent, detailed reports. Important strategic decisions were never delegated. The major conclusion is that long hours of work are not essential for entrepreneurial success and may under certain circumstances be counter productive.
Keywords: Entrepreneurship; Leisure